Methods in heritage language research: Reflections from the 14th Workshop on Immigrant Languages in the Americas (WILA) - Kühl, Karoline; Litty, Samantha M. (Bergen Language and Linguistics Studies, 2025)
This introductory paper by the WILA 14 conference organizers introduces the WILA 14 conference theme, “Methods”, and serves as an overview of methods currently used in heritage language research, a discussion of methodological consideration necessary for conducting research, and includes suggestions and food for thought for both novice and experienced heritage language researchers. Discussions regarding methods and methodological choices from WILA 14 have been incorporated into this paper, and examples are drawn from the papers contained in this volume.